Time budgets and their uses - Andorka, Rudolf; East-West Environment and Policy Institute; Southeast Asian Universities Agroecosystem Network; SUAN Information Support Service; Ford Foundation; East-West Center (1987)
The paper summarizes the state of the art of time budget survey and analyses. It firsts treats the new methodological developments, than reviews the different fields of utilization of time budget data; mass media contact, demand for cultural and other leisure goods and services, urban planning, consumer behavior, needs of elderly persons and of children, the sexual division of labor, the informal economy and household economics, social accounting, social indicators; quality of life, social structure. It deals also with the lessons from intertemporal and international comparisons of the results of time budget surveys.
Introduction -- Methodology -- Fields of utilization: Mass media contact, demand for cultural and other leisure goods and services; Urban planning; Consumer behavior; The needs of elderly persons and the care of children; The sexual division of labor; The informal economy and household economics; Social accounting, social indicators, well-being, quality of life; The exploration of the "style of life"; Social structure; Intertemporal and international comparison -- Concluding remarks.
Photocopy.
This document has been provided by EAPI as part of its SUAN Information Support Service. The goal of this service is to make current literature relating to human ecology and agroecosystems research available to scientists participating in the Southeast Asian Universities Agroecosystem Network. Partial funding for this service is provided by a Ford Foundation grant to the East-West Center.
Includes bibliographical references (pages 162-164).
Keywords: Time management; Research -- Methodology; Quality of life